Oral treatment with Lactobacillus reuteri attenuates depressive-like behaviors and serotonin metabolism alterations induced by chronic social defeat stress. (March 2020) - Xie, Ruining; Jiang, Pei; Lin, Li; Jiang, Jian; Yu, Bin; Rao, Jingjing; Liu, Hui; Wei, Wei; Qiao, Yi
Abstract: Background: Alterations in bidirectional gut–brain interactions are believed to be involved in the pathogenesis of neuropsychiatric diseases. Considering the putative connections among gut microbiota, neural function, and behavior, this study investigated the potential of microbe-induced gut–to–brain signaling to modulate the impact of stress on depressive-like behaviors and serotonin metabolism. Methods: Depression-susceptible mice induced by chronic social defeat stress received oral treatment of either Lactobacillus reuteri 3 ( L. reuteri 3) or vehicle for 28 days, and alterations in behavior and serotonin metabolism were assessed. 16S rRNA sequencing and gas chromatograph were employed to analyze the gut microbiota community and short-chain fatty acids (SCFAs). Results: Treatment with L. reuteri 3 ameliorated depressive-like behaviors, suppressed the increase in the relative abundances of Clostridiales and Adlercreutzia, improved the decrease in abundances of Lactobacillus, Allobaculum, and Sutterella induced by stress, and significantly increased the proportion of Bifidobacterium . L. reuteri 3 reduced the acetate and total SCFAs levels in the depression group. Blood and colon 5-HT were decreased in depressive-like mice but were significantly ameliorated after L. reuteri 3 treatment. Moreover, L. reuteri 3 administration increased the expression of enzymes involved in serotonin biosynthesis but suppressed that of the enzymes involved in tryptophan metabolism along the kynurenine pathway in colon and prefrontal cortex. Conclusions: Despite the complexity of the gut microbiota, exposure to a single microbial strain L. reuteri 3 can protect against depressive-like behaviors induced by chronic social defeat stress. The anti-depressive effects of L. reuteri 3 were associated with improved gut microbiota and serotonin metabolism. Graphical abstract: Image 1